PERANCANGAN DAN IMPLEMENTASI ALAT PENGUKUR KARDUS SECARA OTOMATIS - Utama, Hadian Satria; Mardjoko, Pono Budi; Sujono, Mardiyanto (TESLA Jurnal Teknik Elektro UNTAR, 2007)
Measuring the size of box is essential in the box production process. For this reason, it needs the system which can measure the size of box automatically. This paper discuss the designing and implementation of automatic box measurement to help the employee minimize error of box measurement. Due to the result of verification process, system can work properly as the design specifications.